2020
DOI: 10.25105/jkgt.v2i1.7503
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Ethanol, Hexane And Water Extracts Of Clinacanthus Nutans Leaves On Hone-1 Proliferation

Abstract: <p><strong><em>Background:</em></strong><em> </em><em>Mortality from cancer has increased especially in the developing country. Global pattern shows the half of mortality occurred in Asia. One type of cancer occurring in Indonesia is nasopharyngeal cancer. Clinacanthus nutans is a species of herbal plants in the Acanthaceae family that grows in tropical Asia, especially Indonesia. This plant is considered as one of traditional medicinal plants, which is effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…21 Previous research also found that hexane extract of C. nutans leaves can inhibit the proliferation of HONE-1 cell strains (epithelial tumors) by up to 61% because terpenoids in hexane extract has anticancer effects. 31 In this study, the concentration of 500 μg/mL was the most effective concentration in inhibiting migration and inducing apoptosis overall as this concentration had an effect by the 6th hour. Compared to the positive control group, the concentration of 500 μg/mL was more effective because by the 6 th hour the positive control group had not induced apoptosis.…”
Section: Discussionmentioning
confidence: 71%
“…21 Previous research also found that hexane extract of C. nutans leaves can inhibit the proliferation of HONE-1 cell strains (epithelial tumors) by up to 61% because terpenoids in hexane extract has anticancer effects. 31 In this study, the concentration of 500 μg/mL was the most effective concentration in inhibiting migration and inducing apoptosis overall as this concentration had an effect by the 6th hour. Compared to the positive control group, the concentration of 500 μg/mL was more effective because by the 6 th hour the positive control group had not induced apoptosis.…”
Section: Discussionmentioning
confidence: 71%